2017
DOI: 10.1007/s10068-017-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ethanol in soy sauce using electronic nose for halal food certification

Abstract: The purpose of this study was to analyze ethanol content in soy sauce using mass spectrometry (MS) with electronic nose (e-nose) to determine if MS e-nose can replace gas chromatographic analysis for halal certification. Gas chromatography-flame ionization detector (GC-FID), the standard method of ethanol content, was used to analyze 24 different kinds of soy sauce. Ethanol was detected from 13 soy sauce samples in the concentration range of 0.0004-1.7wt%. The MS e-nose data were analyzed by discriminant funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…In the area of Halal, major reported articles have explored the attitude of the consumers towards Halal-certified products (Ali, Ali and Sherwani, 2017; Ariffin and Wahid, 2017; Aziz and Chok, 2013; Bashir et al , 2018; Ali, Xiaoling, Sherwani and Ali, 2017; Izberk-Bilgin and Nakata, 2016; Lestari et al , 2018), their biological and chemical aspects to establish integrity and quality of Halal meat (Park et al , 2017; Premanandh and Bin Salem, 2017; Aghwan et al , 2016; Al-Kahtani et al , 2017; Farouk et al , 2014) and parametric evaluation of effect of stunning on ritually slaughtered animals and their welfare (Fuseini et al , 2016; Rahman, 2017; Nakyinsige et al , 2013; Grandin, 2010; Farouk et al , 2016; Farouk, 2013). However, it is observed that only the recently published literature have focussed on managing operational activities of Halal products (Khan, Khan, Haleem and Jami, 2019; Khan, Haleem and Khan, 2018; Zulfakar et al , 2018; Alzeer et al , 2018; Soon et al , 2017; Haleem and Khan, 2017) and on developing Halal standards as a contemporary standard taking modern lifestyle into consideration (Ahmad et al , 2018; Chandia and Soon, 2018; Talib et al , 2017; Muhamad et al , 2017; Butt et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the area of Halal, major reported articles have explored the attitude of the consumers towards Halal-certified products (Ali, Ali and Sherwani, 2017; Ariffin and Wahid, 2017; Aziz and Chok, 2013; Bashir et al , 2018; Ali, Xiaoling, Sherwani and Ali, 2017; Izberk-Bilgin and Nakata, 2016; Lestari et al , 2018), their biological and chemical aspects to establish integrity and quality of Halal meat (Park et al , 2017; Premanandh and Bin Salem, 2017; Aghwan et al , 2016; Al-Kahtani et al , 2017; Farouk et al , 2014) and parametric evaluation of effect of stunning on ritually slaughtered animals and their welfare (Fuseini et al , 2016; Rahman, 2017; Nakyinsige et al , 2013; Grandin, 2010; Farouk et al , 2016; Farouk, 2013). However, it is observed that only the recently published literature have focussed on managing operational activities of Halal products (Khan, Khan, Haleem and Jami, 2019; Khan, Haleem and Khan, 2018; Zulfakar et al , 2018; Alzeer et al , 2018; Soon et al , 2017; Haleem and Khan, 2017) and on developing Halal standards as a contemporary standard taking modern lifestyle into consideration (Ahmad et al , 2018; Chandia and Soon, 2018; Talib et al , 2017; Muhamad et al , 2017; Butt et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ethanol in soy sauce production is used for stabilizing the quality and adding flavor and is generally found at various concentrations in soy sauces (20). The higher ethanol concentrations in some soy sauce products may be due to continued enzymatic activity during longterm storage (29). Similar to soy sauces, approximately 4% of all the concentrated syrup samples in the present study had a higher percentage of ethanol than permitted for Halal products.…”
Section: Discussionmentioning
confidence: 59%
“…Ethanol concentration levels ranging from 0.5‰ to 2.5% or even higher have been measured. These products include, for instance, homemade mead and beer, kefir, mursik milk, soy sauce, kimchi, pickled food, and vinegar [25][26][27][28]. Alcohol is often also added to marinades, fondues, salads, and sushi, but the ethanol concentration of the end product served is not known.…”
Section: Low Alcohol Levels In Food and Beverages: Significant Epidemmentioning
confidence: 99%